Free or Monitored?: The Panopticon System in Indonesian Media Reporting - Abdillah Habibi; Rahman Malik (Komunika, 2026)
ABSTRACT The rapid development of news media due to technology in Indonesia indicates the presence of panopticon practices within it. Therefore, this research aims to delve deeper into how the panopticon practice exists in media reporting and to find out whether every individual in society is actually monitored or free in their life due to this practice. This research is a descriptive qualitative study with literature review and digital observation as data collection methods. This research shows that out of the three news articles used as examples of panopticon practices in the media, two of them explain that every behavior and action of individuals in society will always be monitored, even in trivial private matters. Meanwhile, the remaining one explains that the media practices the panoptic method by instilling discipline through widespread reporting to the public regarding the behavior of individuals who oppose or do not conform to the system. The author concludes that the panoptic practice in the media shows constant surveillance of individuals in society, so individuals are actually not free and will always be monitored by news media. Keyword: Media; Panopticon; News Report